PENGARUH SENSORY MARKETING, HARGA DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN DI AHBAB STORE PONTIANAK DALAM PERSPEKTIF BISNIS SYARIAH - Alya, Zulaiha Zahra; Anshori, Aiyub; Nurlia (Tujjar International Journal of Islamic Economics Development, 2026)
Growing awareness among Muslim consumers who increasingly seek shopping experiences that are not merely functional but also spiritually meaningful has compelled businesses to adopt more holistic marketing strategies. This study examines the influence of sensory marketing, price, and product quality on customer satisfaction at Ahbab Store Pontianak, framed within the Sharia business perspective. A quantitative causal-associative design was employed, involving 100 respondents selected through purposive sampling from the store's loyal customer base. Data were collected via a five-point Likert-scale questionnaire and analysed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The measurement model demonstrated satisfactory convergent validity (AVE > 0.50) and reliability (Composite Reliability > 0.70) across all constructs. The R-Square value of 0.539 indicates moderate explanatory power. Bootstrapping results confirm that all three variables exert a positive and significant influence on customer satisfaction: sensory marketing (β = 0.475; t = 6.551; p = 0.000), price (β = 0.395; t = 5.503; p = 0.000), and product quality (β = 0.351; t = 5.277; p = 0.000). Sensory marketing emerged as the strongest predictor, affirming that Islamically-designed sensory experiences such as Quranic recitation, bukhoor fragrance, and Islamic visual aesthetics can substantially shape customer satisfaction. These findings contribute to Islamic marketing theory and offer actionable guidance for Sharia-based SMEs in developing ethically grounded and commercially effective marketing strategies. Keyword: Sensory Marketing; Price; Product Quality; Customer Satisfaction; Sharia Business